We know that:
- y varies directly as x
- y = 6 when x= 3
And we must find y when x = 9
To find it:
1. we must use that y varies directly as x
![y=kx](https://img.qammunity.org/2023/formulas/mathematics/college/zfnjlk9kn7jg7cyy0nlnepmsiaxj3b2oge.png)
2. We must find k using that y = 6 when x = 3
![\begin{gathered} 6=k\cdot3 \\ k=(6)/(3) \\ \Rightarrow k=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6wll1drpw6gosqba025ft9r43yila3pztz.png)
3. Finally, to find y when x = 9 we must replace x = 9 and k = 2 to solve it for y
![\begin{gathered} y=2\cdot9 \\ y=18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c17lhgfazxvwim3hmgmr201q5p9wgmnoel.png)
ANSWER:
y = 18 when x = 9